Breast Tissue Chemistry Measured In Vivo In Healthy Women Correlate with Breast Density and Breast Cancer Risk. Issue 5 (23rd March 2022) - Santamaría, Gorane; Naude, Natali; Watson, Julia; Irvine, John; Lloyd, Thomas; Bennett, Ian; Galloway, Graham; Malycha, Peter; Mountford, Carolyn
Abstract : Background: The relationship of tissue chemistry to breast density and cancer risk has not been documented despite breast density being a known risk factor. Purpose: To investigate whether distinct chemical profiles associated with breast density and cancer risk are identified in healthy breast tissue using in vivo two‐dimensional correlated spectroscopy (2D COSY). Study Type: Prospective. Population: One‐hundred‐seven participants including 55 at low risk and 52 at high risk of developing breast cancer. Field Strength/Sequence: 3 T/ axial/ T1, T2, 2D COSY. Assessment: Two radiologists defined breast density on T2. Interobserver variability assessed. Peak volumes normalized to methylene at (1.30, 1.30) ppm as internal shift reference. Statistical Tests: Chi‐squared/Mann–Whitney/ Kappa statistics/Kruskal Wallis/pairwise analyses. Significance level 0.05. Results: Ten percentage were fatty breasts, 39% scattered fibroglandular, 35% heterogeneously dense, and 16% extremely dense. Interobserver variability was excellent ( kappa = 0.817). Sixty percentage (64/107) were premenopausal. Four distinct tissue chemistry categories were identified: low‐density (LD)/premenopausal, high‐density (HD)/premenopausal, LD/postmenopausal, and HD/postmenopausal. Compared to LD, HD breast chemistry showed significant increases of cholesterol (235%) and lipid unsaturation (33%). In the low‐risk category, postmenopausal women with dense breasts recorded the largest significant changes including cholesterol methyl 540%, lipid unsaturation 207%, glutamine/glutamate 900%, and choline/phosphocholine 800%. In the high‐risk cohort, premenopausal women with HD recorded a more active chemical profile with significant increases in choline/phosphocholine 1100%, taurine/glucose 550% and cholesterol sterol 250%. Data Conclusion: Four distinct chemical profiles were identified in healthy breast tissue based on breast density and menopausal status in participants at low and high risk. Gradual increase in neutral lipid content and metabolites was noted in both risk groups across categories in different order. In low risk, the HD postmenopausal category exhibited the highest metabolic activity, while women at high risk exhibited the highest lipid content and metabolic activity in the HD premenopausal category. Level of Evidence: 2 Technical Efficacy Stage: 3